Maximizing the power of deep extragalactic imaging surveys with the James Webb Space Telescope. Issue 3 (24th April 2019) - Kemp, T W; Dunlop, J S; McLure, R J; Schreiber, C; Carnall, A C; Cullen, F
Abstract: We present a new analysis of the potential power of deep, near-infrared, imaging surveys with the James Webb Space Telescope ( JWST ) to improve our knowledge of galaxy evolution. In this work we properly simulate what can be achieved with realistic survey strategies, and utilize rigorous signal-to-noise ratio calculations to calculate the resulting posterior constraints on the physical properties of galaxies. We explore a broad range of assumed input galaxy types (>20 000 models, including extremely dusty objects) across a wide redshift range (out to z ≃ 12), while at the same time considering a realistic mix of galaxy properties based on our current knowledge of the evolving population (as quantified through the Empirical Galaxy Generator). While our main focus is on imaging surveys with NIRCam, spanningλ _ obs = 0.8\!-\!5.0 μ m, an important goal of this work is to quantify the impact/added-value of: (i) parallel imaging observations with MIRI at longer wavelengths, and (ii) deeper supporting optical/UV imaging with HST (potentially prior to JWST launch) in maximizing the power and robustness of a major extragalactic NIRCam survey. We show that MIRI parallel 7.7-μ m imaging is of most value for better constraining the redshifts and stellar masses of the dustiest ( AV > 3) galaxies, while deep B -band imaging (reaching ≃ 28.5 AB mag) with ACS on HST is vital for determining the redshifts of the large numbers of faint/low-mass, z < 5 galaxies that will be detected in a deep JWST NIRCam survey.